2004
DOI: 10.1300/j002v36n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Adolescents' Decision-Making, Parent-Adolescent Communication and Relationships

Abstract: The present study described Mainland Chinese adolescents' decision-making, and examined the relationship among their decision-making involvement, parent-adolescent communication and relationship variables by using Structural Equation Modeling. Results demonstrated that Chinese parents appeared to be less authoritarian than the prevailing literature had described. Chinese adolescents experienced a passage of autonomy development similar to that of their American counterparts. Good parent-adolescent communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…In the present study, the latent construct of parent-child relationship quality included authoritative parenting style, parent-child communication, and relationship cohesion. This conceptualization of the parent-child relationship is consistent with current research indicating that Chinese parents are increasingly adopting a parenting style that is warm and attentive and allows for joint decision making (Chen & Li, 2012;Xia et al, 2004 Finally, our results suggest that this model is largely consistent regardless of the gender of the parent and the gender of the child and whether parents reside in a district of the city labeled as urban versus rural. Although the model fit well for all groups tested, the path between cultural beliefs and engagement in sexuality education was not as strong for parents of boys.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, the latent construct of parent-child relationship quality included authoritative parenting style, parent-child communication, and relationship cohesion. This conceptualization of the parent-child relationship is consistent with current research indicating that Chinese parents are increasingly adopting a parenting style that is warm and attentive and allows for joint decision making (Chen & Li, 2012;Xia et al, 2004 Finally, our results suggest that this model is largely consistent regardless of the gender of the parent and the gender of the child and whether parents reside in a district of the city labeled as urban versus rural. Although the model fit well for all groups tested, the path between cultural beliefs and engagement in sexuality education was not as strong for parents of boys.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the latent construct of parent-child relationship quality included authoritative parenting style, parent-child communication, and relationship cohesion. This conceptualization of the parent-child relationship is consistent with current research indicating that Chinese parents are increasingly adopting a parenting style that is warm and attentive and allows for joint decision making (Chen & Li, 2012;Xia et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Also, Yue and Ng (1999) found that young people tended to endorse high respect for elders but not obedience. Taken together, Chinese adolescent children demand autonomy and independence, and Chinese parents, willingly or not, need to negotiate with their children regarding everyday authority issues, which is not much different from the typically depicted Western family (Xia et al, 2004). Nonetheless, Chinese children might consider attentive parental monitoring and organization, instead of expressive affection, as indicative of parental love and warmth (Bush, Peterson, Cobas, & Supple, 2002).…”
Section: Social Confucianism: Contemporary Practices In Chinese Parenmentioning
confidence: 99%